Réactions de type «Claisen» avec le phytol et l'isophytol - J.P. Marion; Y. Bessière-Chrétien (CHIMIA)
We have studied Cabroll, Claisen, Marbet and Saucy reactions with phytol and isophytol. Acetylacetoacetate, dimethyl acetamide-dimethyl acetal and ethyl-vinyl-ether are some of the reagents brought in to reaction. Of the obtained ketones, amides and aldehydes all, except one, are new compounds; their caracteristics are given in detail (IR, NMR, MS).